The Application of The Creative Multiplicity: Black Box and Glass Box Stages in Songwriting Activities at PKBM Omah Dongeng Marwah - Gusti, Tsaqiva Kinasih (Jurnal Seni Musik, 2023)
Creativity does not start from a rational and systematic mind. Creativity multiplicity believes that creative activities and products start from an 'infinite', dynamic, accepting of possibilities, random, disorganized and chaotic thinking structure. This stage is referred to as the 'black box', which then proceeds to a leap of understanding as the mind manages the disorder. The second stage is the 'glass box', where the information in the mind only gets a rational stage through a planned process of analysis, synthesis, and evaluation. The black box and glass box creative processes of the multiplicity creativity concept were tested in songwriting activities at PKBM Omah Dongeng Marwah. The method used in this research is qualitative. The primary data came from systematic, participatory, and experimental observations of songwriting activities at PKBM Omah Dongeng Marwah. The data is summarized through the process of data analysis, synthesis and reduction. As a result, learners are more involved in a holistic and humanistic process. 11 learners aged 15-17 years at PKBM Omah Dongeng Marwah succeeded in creating original songs with their uniqueness and character, so that the process of creating songs through the stages of black box and glass box creativity was said to be successful.